Peranan Pembelajaran Pendidikan Agama Islam di Lingkungan Sekolah Terhadap Sikap Toleransi Beragama SMPN 02 Sumowono - Aisha Mirani; Junedi; Mukh Nursikin (Rihlah Review: Jurnal Pendidikan Islam, 2022)
The result of this study indicates that the understanding and religious tolerance in the school environment towards religious tolerance at middle school students 02 in Sumowono. Qualitative methods were used in this study with survey techniques presented in a qualitative descriptive manner. Data were collected through interviews and observations involving 25 students. Sources of data include primary source obtained from informants, namely teachers and educators. The results of this study are Islamic religious education in the school environment towards the attitude of religious tolerance at middle school students 02 in Sumowono shows that there are: (1) tolerance for school residents (2) recognition between differences, among others and with other religions. (3) always respect adherents of other religions. (4) does not discriminate from the background. (5) the atmosphere in the school is created conducive and harmonious.